The effect of electrode materials on Pb alloy superconducting tunnel junctions for submillimetre wave heterodyne receiver application - Claude, SMX; Moon, SW (IOP PUBLISHING LTD, 1997)
Submicron superconducting tunnel junctions were fabricated for submillimetre wavelength heterodyne detection. To this end three types of Pb alloy electrodes were investigated. All have shown good I-V do characteristics but only the Pb-In-Au alloy produced stable and reliable junctions in vacuum and thermal cycling. Au-free junctions were found to be unreliable and would fail, i.e would form a short circuit, when placed in vacuum by desorption of water from the oxide barrier. This effect was subsequently stopped by alloying the electrode with 1% wt of Au leading to cathodic corrosion which in turn protects the junction from failing in vacuum.
Keywords: FILMS